1983
DOI: 10.1172/jci111086
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpropamide action on renal concentrating mechanism in rats with hypothalamic diabetes insipidus.

Abstract: A B S T R A C T To determine vasopressin (VP)-potentiating effect of chlorpropamide (CPMD), we studied the effect of CPMD in vivo and in vitro in kidneys and in specific tubule segments of rats with hypothalamic diabetes insipidus, homozygotes of the Brattleboro strain (DI rats). Rats on ad lib. water intake were treated with CPMD (20 mg/100 g body wt s.c. daily) for 7 d. While on ad lib. water intake, the urine flow, urine osmolality, urinary excretion of Na+, K+, creatinine, or total solute excretion did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 58 publications
(145 reference statements)
0
30
0
Order By: Relevance
“…Zusman et al (1977) showed that CPM enhanced ADH-stimulated water flow by inhibiting prostaglandin E production in the toad urinary bladder. On the other hand, Kusano et al (1983) showed the CPM did not augment cAMP-mediated water permeability in the kidney of the Brattleboro rats, and increased the renal osmotic gradient in the renal medulla in the presence of ADH. However, these concepts might be only feasible, if any, in the presence of APR release despite the hyponatremic state.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Zusman et al (1977) showed that CPM enhanced ADH-stimulated water flow by inhibiting prostaglandin E production in the toad urinary bladder. On the other hand, Kusano et al (1983) showed the CPM did not augment cAMP-mediated water permeability in the kidney of the Brattleboro rats, and increased the renal osmotic gradient in the renal medulla in the presence of ADH. However, these concepts might be only feasible, if any, in the presence of APR release despite the hyponatremic state.…”
Section: Discussionmentioning
confidence: 86%
“…CPM may enhance the release of vasopressin (ADH) from the central nervous system (CNS), increase the production of renal cyclic AMP in response to ADH and the formation of renal medullary osmotic gradient, thereby resulting in enhanced urine concentration (Miller and Moses 1970b; Beck et al 1974; Moses and Coulson 1980;Moses et al 1982; Kusano et al 1983). …”
mentioning
confidence: 99%
“…Tubular segments were microdissected from the canine kidney in a similar manner as in our other studies of nephrons from other mammalian species (20)(21)(22)(23)(24). Kidneys were taken from the mongrel dogs, anesthetized with pentobarbital, and immediately perfused with heparinized ice-cold collagenase medium.…”
Section: Methodsmentioning
confidence: 99%
“…After the perfusion with heparinized collagenase medium, the cortical tissue was sliced with a razor blade and the pieces of tissue were incubated in aerated collagenase medium at 350C for 50-70 min, which was similar to our previous studies (20)(21)(22). After incubation, the slices were thoroughly rinsed in ice-cold microdissection medium and transferred to Petri dishes for microdissection.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that CPM decreases the inhibitory effect of prostaglandins on ADH-dependent generation of cyclic AMP (Ozer & Sharp, 1973) but Omachi et al (1974) have shown that CPM lowers cyclic AMP levels in toad urinary bladder in response to ADH. Ozer & Sharp, (1973) have interpreted the potentiating effect of CPM upon ADH in toad urinary bladder as the consequence of raising levels of intracellular cyclic AMP; while Kusano et al (1983) proposed that CPM enhances the effect of ADH by a mechanism that increases the osmotic driving force for water reabsorption in collecting tubules.…”
Section: Effect Of Chlorpropamidementioning
confidence: 99%